2014
DOI: 10.1556/achrom.26.2014.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting thin-layer chromatography as a lipophilicity determination tool. Part IV — A closer look on extrapolation and averaging

Abstract: Summary. The paper compares linear, quadratic, and cubical regression together with several weighted and robust approaches in the context of lipophilicity determination. The comparison is done on 35 model compounds on data from different modifiers used on RP18, CN, and silica plates. It can be concluded that the use of weighted and moderately robust regression technique increases correlation between extrapolated retention and real lipophilicity, whereas polynomial and very robust techniques give visibly worse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This curvilinearity is very similar among the investigated compounds, so relative differences of extrapolated R M are almost the same regardless of the regression technique used. However, different adsorption mechanism can cause strong relative differences among the investigated compounds and between regression techniques, which was proven in an earlier study [13] in reversed-phase sys- tems. Therefore, it can be concluded that (summarizing previous and current results) one should primarily consider weighted regression with 1/x weights (WLM) during retention extrapolation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This curvilinearity is very similar among the investigated compounds, so relative differences of extrapolated R M are almost the same regardless of the regression technique used. However, different adsorption mechanism can cause strong relative differences among the investigated compounds and between regression techniques, which was proven in an earlier study [13] in reversed-phase sys- tems. Therefore, it can be concluded that (summarizing previous and current results) one should primarily consider weighted regression with 1/x weights (WLM) during retention extrapolation.…”
Section: Resultsmentioning
confidence: 91%
“…Only two papers describe comprehensive comparison of adsorption and retention models [11,12]. Some model compounds and drugs of simple molecule were investigated by us earlier in context of lipophilicity extrapolation [13], and this paper can be treated as a continuation of the topic. Chromatography was performed on silica gel TLC 60 F 254 plates (Merck) using horizontal DS Chambers (Chromdes, Lublin, Poland) in horizontal mode.…”
Section: Introductionmentioning
confidence: 99%
“…The extrapolated R M0 data on RP18 plates (R) and CN plates (C) were recomputed by least trimmed squares regression from our two earlier papers [2,4]. For each adsorbent, six modifiers: acetonitrile (1), acetone (2), dioxane (3), propan 2-ol (4), methanol (5), and tetrahydrofurane (6) were used in the investigations.…”
Section: Methodsmentioning
confidence: 99%
“…The last part of our study was an extensive comparison of extrapolation and averaging techniques between modifiers [5]. The use of weighted and moderately robust regression technique increased correlation between extrapolated retention and shake-flask lipophilicity.…”
Section: Introductionmentioning
confidence: 99%